Isolation and purification of bacterial strains from treatment plants for effective and efficient bioconversion of domestic wastewater sludge - Jalal, K. C. A.; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen (Science Publications, 2006)
Forty six bacterial strains were isolated from nine different sources in four treatment plants namely Indah Water Konsortium (IWK) sewage treatment plant, International Islamic University Malaysia (IIUM) treatment plant-1,-2 and –3 to evaluate the bioconversion process in terms of efficient biodegradation and bioseparation. The bacterial strains isolated were found to be 52.2% (24 isolates) and 47.8% (22 isolates) in the IWK and IIUM treatment plants respectively. The results showed that the higher microbial population (9-10x104 cfu mL1) was observed in the secondary clarifier of IWK treatment plant. Only the gram-staining identification was done in the strains isolated from IWK treatment plant not to be determined from IIUM. Among the isolates from IWK, 10 isolates of gram-positive bacillus (GPB) and gram-positive cocci (GPC), 10 isolates of gram-negative bacillus (GNB) and rest were both or undetermined. Gram-negative cocci (GNC) were not found in the isolates from IWK.